WARISAN BUDAYA MILITER BIROKRASI DALAM PROSES REKRUTMEN DI INDONESIA: Studi Kasus Kemenko Polhukam RI - Putri Khoirunnisa (2022)
This study discusses the relationship between military organizations in the civilian realm which is still found in Indonesia, seen in the bureaucracy at the Coordinating Ministry for Political, Legal and Security Affairs of the Republic of Indonesia. Military involvement is a historical consequence and has an impact on the prevailing bureaucratic culture. This study uses descriptive qualitative data collection techniques through interviews, observations and literature studies. The final result of this study found that; 1) Military involvement in civilian positions is a legacy of the military regime that once ruled, 2) In the pattern of the recruitment process, efforts to place or link military organizations still exist by applying old patterns, 3) The prevailing military culture in civil-military relations is still very attached.